Food Consumption Pattern of Farming Families in Punjab - Vij, Abhishek; Mann, Sukhdeep Kaur (Indian Journal of Extension Education, 2022)
The  study was conducted in Punjab state to analyze the food consumption pattern of farming families. Empirical data was collected from  180 respondents i.e. 60 males, 60 females and 60 children from farming families of Punjab with the help of a selfstructured interview schedule. Findings revealed that cent per cent of the respondents had their breakfast and dinner daily. Further, it was found that there was a low consumption of fruits and nuts & oil seeds in the majority of the respondents and high consumption of fats & oils in nearly half of the respondents. The frequency of consumption of all the other food groups was found to be in medium category. The mean frequency consumption of milk & milk products, other vegetables (non-green leafy vegetables) and non-vegetarian food showed significant differences between the three categories of respondents. An imbalance was found in the consumption of different food groups by the respondents. So, based on the findings of the research, the paper recommends that there is a need for special efforts to change the consumption pattern of farming families in Punjab and spread awarenessamong the population to include a variety of food items from different food groups in the  diet.